Effectiveness of Salvadora persica toothbrush and Salvadora persica chewing stick in plaque and gingivitis control: a randomized control trial - Nurul Fatin Azizan; Nurulhuda Mohd; Nik Madihah Nik Azis; Badiah Baharin (BMC, 2023)
Abstract Background The values of plant-based products have taken on an expanding relevance in dentistry. Salvadora persica chewing stick (miswak) has been practiced for centuries and is recommended by the World Health Organization as a customary oral hygiene tool. The therapeutic effects of S. persica chewing stick are contributed by its mechanical cleansing action, active chemicals released, or the combination of these two actions. However, the S. persica chewing stick in its natural form can be difficult to maneuver in certain parts of the mouth. This concern has inspired the innovation of the S. persica toothbrush that is designed to merge the ease of use of a toothbrush with the beneficial natural properties of S. persica preserved in its bristle. The present study aimed to compare the clinical effectiveness between S. persica toothbrush, S. persica chewing stick and the standard toothbrush in plaque and gingivitis control. Methods In this single-blinded and parallel randomized controlled trial, 78 participants were randomly divided into three groups to either use (i) S. persica toothbrush (MTB); (ii) S. persica chewing stick (MCS); or (iii) standard toothbrush (STB) in a standardized manner for three weeks. Plaque Index (PI) and Periodontal Inflamed Surface Area (PISA) values, measuring plaque levels and severity of gingivitis, respectively, were evaluated at baseline, one- and three-week post-interventions. Results The MCS group showed a significant improvement in the mean PISA values of the anterior teeth compared to the MTB and STB groups (MCS: from 16.35 ± 10.03 to 3.41 ± 1.14; MTB: from 25.20 ± 14.01 to 3.57 ± 1.19; STB: from 26.54 ± 8.64 to 6.17 ± 0.86; p < .050). All three groups reported significant improvements (p < .001) in the plaque levels and the severity of gingivitis from baseline to three weeks after the intervention. Conclusions Following correct techniques, S. persica toothbrush and chewing sticks are as effective as the standard toothbrush in plaque control and gingival health, which represent the reputed anti-plaque and anti-gingivitis properties of S. persica. Trial registration This clinical trial was prospectively registered in ClinicalTrials.gov with registration NCT04650685 (25/11/2020).